FACTORS AFFECTING THE COMMUNITY HABITS UTILIZING AIR BATANG KENAGARIAN SALISIKAN AT REED RIVER DISTRICT BATANG ANAI PARIAMAN DISTRICT. GEOGRAPHY EDUCATION: STKIP PGRI WEST SUMATERA - Mayasari, Vela; Dasrizal, Dasrizal; Zuriyani, Elvi (Pendidikan Geografi, 2013)
This study aimed to obtain information, analyze and discuss data on the factors that influence peoples habits in using Salisikan in Kenagarian Air Batang River District Batang Anai Reed Pariaman district. This type of research is descriptive correlational. The study population was the head of household or family who live between 0-200 m of Air Batang Kenagarian Salisikan at Reed River District Batang Anai Pariaman district, amounting to 360 households in the study sample is proportional random sampling technique is the proportion of 15% that sample of around 54 households. Based on a simple linear regression analysis, a double (multiple) and the correlation it can be concluded as follows: (1) There is the influence of the educational level of the people in the habit of utilizing Air Batang Salisikan the enormous impact that lower category (r = 0.367) and a very small contribution (13.4%), (2) There is the influence of the level of knowledge of the habits of the people in the use of Air Batang desarnya Salisikan with influences including low category (r = 0.394) and a very small contribution (15.5%), (3) there is an influence between the income level of the people in the habit of utilizing Air Batang Salisikan the enormous impact that includes low (r = 0.386) and a very small contribution (14.9%), (4) There is no effect of the number of family members to the customs of the people in the use of Air Batang Salisikan because the magnitude of the effect is very low (r = 0.147) with a very small contribution (2.2%) and (5) There is the influence of the level of education, level of knowledge, level of income and number of family members together to exploit peoples habits in Batang Air Salisikan in Kenagarian Reed River District Batang Anai Pariaman district because Fhitung> F table (4.824> 3.150) with moderate strength (r = 0.532) and includes a small contribution (28.3%).